2017
DOI: 10.1515/acph-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photodegradation studies of analogues of muscle relaxant 1,4-dihydropyridine compounds

Abstract: This paper describes the synthesis of 1,4-dihydropyridine compounds (DHPs) endowed with good muscle relaxant activity and stability to light. Six new condensed DHPs were synthesized by the microwave irradiation method. A long-chain ester moiety [2-(methacryloyloxy)ethyl] and various substituents on the phenyl ring were demonstrated to aff ect the muscle relaxant activity occurring in isolated rabbit gastric fundus smooth muscle strips. Forced photodegradation conditions were applied to the molecules according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In any case, the photodegradation process involves the total loss of the therapeutic effect. Unfortunately, it is also known that the photodegradation of the DHP drugs leads to a significant production of singlet oxygen, superoxide, or both of them, which in most cases are responsible for photosensitive/phototoxic effects [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the photodegradation process involves the total loss of the therapeutic effect. Unfortunately, it is also known that the photodegradation of the DHP drugs leads to a significant production of singlet oxygen, superoxide, or both of them, which in most cases are responsible for photosensitive/phototoxic effects [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that the main photodegradation pathway of dihydropyridine drugs such as amlodipine and nifedipine was the oxidation of dihydropyridine rings resulting in the generation of pyridine derivatives [39][40][41]. However, as shown in Fig.…”
Section: The Photodegradability Evaluation Of Apis By Hplcmentioning
confidence: 99%
“…Several approaches have been proposed to design liquid pharmaceutical formulations of DHPs: addition of excipients with large absorption regions, incorporation in supramolecular matrices as liposomes or cyclodextrins, and incorporation in microspheres or nanocapsules [18,19]. A different approach involves the synthesis of new DHP structures more stable to oxidation [20]. However, today the adoption of dark glass or plastic containers remains the most common method used by the pharmaceutical industry to protect photosensitive drugs.…”
Section: Introductionmentioning
confidence: 99%